New Inhibitors of Bcr-Abl Based on 2,6,9-Trisubstituted Purine Scaffold Elicit Cytotoxicity in Chronic Myeloid Leukemia-Derived Cell Lines Sensitive and Resistant to TKIs - Thalia Delgado; Denisa Veselá; Hana Dostálová; Vladimír Kryštof; Veronika Vojáčková; Radek Jorda; Alejandro Castro; Jeanluc Bertrand; Gildardo Rivera; Mario Faúndez; Miroslav Strnad; Christian Espinosa-Bustos; et al. (MDPI AG, 2024)
Bcr-Abl is an oncoprotein with aberrant tyrosine kinase activity involved in the progression of chronic myeloid leukemia (CML) and has been targeted by inhibitors such as imatinib and nilotinib. However, despite their efficacy in the treatment of CML, a mechanism of resistance to these drugs associated with mutations in the kinase region has emerged. Therefore, in this work, we report the synthesis of 14 new 2,6,9-trisubstituted purines designed from our previous Bcr-Abl inhibitors. Here, we highlight 11b, which showed higher potency against Bcr-Abl (IC50 = 0.015 μM) than imatinib and nilotinib and exerted the most potent antiproliferative properties on three CML cells harboring the Bcr-Abl rearrangement (GI50 = 0.7-1.3 μM). In addition, these purines were able to inhibit the growth of KCL22 cell lines expressing Bcr-AblT315I, Bcr-AblE255K, and Bcr-AblY253H point mutants in micromolar concentrations. Imatinib and nilotinib were ineffective in inhibiting the growth of KCL22 cells expressing Bcr-AblT315I (GI50 > 20 μM) compared to 11b-f (GI50 = 6.4-11.5 μM). Molecular docking studies explained the structure-activity relationship of these purines in Bcr-AblWT and Bcr-AblT315I. Finally, cell cycle cytometry assays and immunodetection showed that 11b arrested the cells in G1 phase, and that 11b downregulated the protein levels downstream of Bcr-Abl in these cells.